13C nuclear magnetic resonance analysis of glucose and citrate end products in an ldhL-ldhD double-knockout strain of Lactobacillus plantarum. - Ferain, T (1996)
We have examined the metabolic consequences of knocking out the two ldh genes in Lactobacillus plantarum using 13C nuclear magnetic resonance. Unlike its wild-type isogenic progenitor, which produced lactate as the major metabolite under all conditions tested, ldh null strain TF103 mainly produced acetoin. A variety of secondary end products were also found, including organic acids (acetate, succinate, pyruvate, and lactate), ethanol, 2,3-butanediol, and mannitol.